2022
DOI: 10.1126/scitranslmed.abj9779
|View full text |Cite
|
Sign up to set email alerts
|

Addition of interleukin-2 overcomes resistance to neoadjuvant CTLA4 and PD1 blockade in ex vivo patient tumors

Abstract: Neoadjuvant immunotherapy with anti-cytotoxic T lymphocyte–associated protein 4 (CTLA4) + anti–programmed cell death protein 1 (PD1) monoclonal antibodies has demonstrated remarkable pathological responses and relapse-free survival in ~80% of patients with clinically detectable stage III melanoma. However, about 20% of the treated patients do not respond. In pretreatment biopsies of patients with melanoma, we found that resistance to neoadjuvant CTLA4 + PD1 blockade was associated with a low CD4/interleukin-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…45 This platform allows interrogation of the early immunological response of human tumor tissues upon ex vivo ICB treatment (aPD1 and combined aPD1 + aCTLA4). Importantly, the observed ex vivo response (defined as described previously 45,46 ) correlates with the clinical response of the patient. 45 We assessed the protein levels of IL-5 upon ex vivo ICB stimulation in tumors of patients with different tumor types.…”
Section: Il-5 Is Required For Icb-induced Eosinophil Accumulation And...mentioning
confidence: 99%
See 2 more Smart Citations
“…45 This platform allows interrogation of the early immunological response of human tumor tissues upon ex vivo ICB treatment (aPD1 and combined aPD1 + aCTLA4). Importantly, the observed ex vivo response (defined as described previously 45,46 ) correlates with the clinical response of the patient. 45 We assessed the protein levels of IL-5 upon ex vivo ICB stimulation in tumors of patients with different tumor types.…”
Section: Il-5 Is Required For Icb-induced Eosinophil Accumulation And...mentioning
confidence: 99%
“…(G) Fold change in IL-5 secretion by PDTF treated ex vivo with aPD-1+aCTLA-4 (left) or aPD-1 (right) compared with untreated condition, measured by LEGENDplex, comparing PDTF-R (responders) and PDTF-NR (non-responders), defined as described previously. 45,46 Tumor samples were collected from surgical material of patients with various tumor types (see STAR Methods and Table S4). S4.…”
Section: Il-5 Is Required For Icb-induced Eosinophil Accumulation And...mentioning
confidence: 99%
See 1 more Smart Citation
“…[143][144][145] The pro-inflammatory cytokine IL-2 enhances the antitumor capacity of chimeric antigen receptor T cells, helping them to overcome the resistance to PD-1 and cytotoxic T lymphocyte antigen 4 (CTLA-4). [146,147] This is because the antitumor immune capacity of many cancer patients is in a "cold" state, and inflammation activates it. Thus, pro-inflammatory cytokines have dual functions.…”
Section: Microbiota-derived Metabolites Affect the Efficacy Of Immuno...mentioning
confidence: 99%
“…Historically, studies have reported diminished T cell reactivity, often demonstrating limited proliferative and cytokine responses [4][5][6]8,9,14,[16][17][18][19]24,26,27,[35][36][37][38][39][40][41] . More current techniques assess multiple cytokines simultaneously to address T cell "polyfunctionality", [42][43][44][45][46][47][48][49][50][51][52][53] which has been linked to outcomes in various tumor types [54][55][56] . We thus used a high-throughput, ELISA-based single-cell cytokine secretion assay to assess T cell polyfunctionality and compared systemic T cell function in the setting of both intracranial and peripheral tumors.…”
Section: Systemic T Cell Function Is Impaired By Catecholamine Surges...mentioning
confidence: 99%